DO BUSINESS CHARACTERISTICS AND ECONOMIC FACTORS AFFECT EFFECTIVE TAX RATE? AN EVIDENCE FROM SOUTHEAST ASIA - Andrey Hasiholan Pulungan; Kenny Fernando; Erma Mei Safa; Annisa Adelia Mahardika (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
The corporate tax burden is known to have a substantial impact on company management and the formation of national policy. One of the ways to measure the tax burden is by using effective tax rate (ETR). Prior research suggests that each region‘s characteristics may influence ETR within the region to varying degrees. Thus, the purpose of this study is to assess the impact of business characteristics and economic factors on ETR in Southeast Asia. There are 852 Southeast Asia companies used as samples in this study. The data is taken from S&P Capital over five periods from 2015-2019 and examined using a random effect regression model by STATA. The findings indicate that business characteristics and economic factors have a limited impact on ETR. By highlighting the factors that affect ETR in Southeast Asia, companies and policymakers can make better tax plans and policies.